Between legal requirements, research and practical application – the assessment of settlement areas in preparatory land-use plans - Schoppengerd, Johanna; Schubert, Katharina (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
The paper analyses the municipal assessment practice for the selection of settlement areas in preparatory land-use planning displays the influence of research results on current planning practice. Based on an analysis of the state of research and the legal framework conditions, the assessment of potential settlement areas for 29 preparatory land-use plans has been analysed. As a result, it was determined that the number of selection criteria and the complexity of the assessment in planning practice has increased significantly in recent years. Furthermore, it became obvious that and to what extend the planning methodology and the criteria applied to select settlement areas differ substantially between the municipalities. Despite extensive application-oriented research in recent years on the assessment and selection of settlement areas, only indirect influences of the research on planning practice can be identified. Nevertheless, the analyses revealed that municipality themselves also created new criteria and procedures.
Keywords: Assessment of settlement areas; Analysis of potential building area; Preparatory Land-use plan; Theory-practice gap